1982
DOI: 10.1111/j.1399-0004.1982.tb01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper/zinc superoxide dismutase (SOD‐1) activity in regular trisomy 21, trisomy 21 by translocation and mosaic trisomy 21

Abstract: Cu/Zn superoxide dismutase (SOD‐1) (E.C.1.15.1.1.) activity was estimated in children with regular trisomy 21‐Down syndrome as well as in cases of translocation and mosaic trisomy 21, as identified by the GTG, CBG and RHG banding techniques. SOD‐1 activity was found to be increased in all examined cases except trisomy 21 mosaicism. These findings provide further proof of the gene dosage theory and additional biochemical evidence for the triplicate existence of the SOD‐1 gene localized on chromosome 21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
(13 reference statements)
2
0
0
Order By: Relevance
“…The erythrocyte MDA levels obtained in these cases are similar to those observed in individuals with DS due to regular trisomy 21. These results are in accordance with those reported by Garber et al (19) and Jeziorowska et al (20), who reported elevated SOD-1 activity in red blood cells in cases of translocation trisomy 21 t(q21q21).…”
Section: Discussionsupporting
confidence: 93%
“…The erythrocyte MDA levels obtained in these cases are similar to those observed in individuals with DS due to regular trisomy 21. These results are in accordance with those reported by Garber et al (19) and Jeziorowska et al (20), who reported elevated SOD-1 activity in red blood cells in cases of translocation trisomy 21 t(q21q21).…”
Section: Discussionsupporting
confidence: 93%
“…It is very difficult at present to define precisely the mental retardation differences among the two presented trisomy 21 groups in association with the different SOD 1 level observed in them, as the children are young and of various ages. Previous reports have suggested that within the general category of Down syndrome, mosaics are likely to be among the brightest group (Johnson & Abelson 1969), and as has been reported previously, SODl activity in the normal range was also found in cases of mosaic trisomy 21 (Jeziorowska et al 1982).…”
Section: Dlscussionsupporting
confidence: 75%